2016
DOI: 10.3762/bjoc.12.180
|View full text |Cite
|
Sign up to set email alerts
|

Unusual reactions of diazocarbonyl compounds with α,β-unsaturated δ-amino esters: Rh(II)-catalyzed Wolff rearrangement and oxidative cleavage of N–H-insertion products

Abstract: SummaryRh(II)-сatalyzed reactions of aroyldiazomethanes, diazoketoesters and diazodiketones with α,β-unsaturated δ-aminoesters, in contrast to reactions of diazomalonates and other diazoesters, give rise to the Wolff rearrangement and/or oxidative cleavage of the initially formed N–H-insertion products. These oxidation processes are mediated by Rh(II) catalysts possessing perfluorinated ligands. The formation of pyrrolidine structures, characteristic for catalytic reactions of diazoesters, was not observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Further, a closer inspection of the results, as listed in Table , implied to us that 3b was also possibly derived from the ketene intermediate that led to 4b , and the competition of the ketene between O 2 and H 2 O might account for the ratios of the two products (as in entries 2 and 6 in Table ). Moreover, extensive investigations have demonstrated that molecular oxygen can be activated by Rh­(I)- or Rh­(II)-complexes through the interaction with a transition-metal center. Accordingly, we assume that the dirhodium­(II) catalyst (simplified as RhL n ) employed in our studies is partially oxidized to a rhodium peroxide or peroxy radical complex ,, upon exposure to oxygen, which are tentatively assigned as cat-O 2 (Rh 2 6+ or Rh 4+ ) and cat-O 2 • (Rh 2 5+ or Rh 3+ ), as shown in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…Further, a closer inspection of the results, as listed in Table , implied to us that 3b was also possibly derived from the ketene intermediate that led to 4b , and the competition of the ketene between O 2 and H 2 O might account for the ratios of the two products (as in entries 2 and 6 in Table ). Moreover, extensive investigations have demonstrated that molecular oxygen can be activated by Rh­(I)- or Rh­(II)-complexes through the interaction with a transition-metal center. Accordingly, we assume that the dirhodium­(II) catalyst (simplified as RhL n ) employed in our studies is partially oxidized to a rhodium peroxide or peroxy radical complex ,, upon exposure to oxygen, which are tentatively assigned as cat-O 2 (Rh 2 6+ or Rh 4+ ) and cat-O 2 • (Rh 2 5+ or Rh 3+ ), as shown in Scheme .…”
Section: Resultsmentioning
confidence: 99%